Pengembangan Media Pembelajaran Berbasis Filmora untuk Materi Drama di Kelas XI Sekolah Menengah Atas Al Washliyah Pasar Senen Medan - Risti Alya Namira; Nila Safina; Ratna Soraya (Education & Learning, 2025)
This study aimed to describe the development process, validation, feasibility, and effectiveness of the using of Indonesian language learning media with drama materials assisted by the Filmora Application in class XI. This study was conducted at SMA Al Washliyah Pasar Senen Medan. This study used the Research and Development (R&D) with ADDIE model developed by Lee and Owens consisting of Analysis, Design, Development, Implementation, and Evaluation with a population as 24 students. The sample in this study used a purposive sampling technique in total as 15 students. The types of data in this study include qualitative and quantitative data. The results of this study are in the form of Indonesian language learning media products with drama material assisted by the Filmora application. Based on the validation results from material expert I, the percentage as 81% or "valid" and material expert II got a percentage as 80% or "valid". Then, the validation results from design expert I got as 91% or "very valid" and design expert II got as "80%" or "valid". The results of teacher responses to drama text learning media by using the Filmora application obtained as 80% or "feasible". Then, the results of student responses obtained as 70% or "quite feasible". It can be concluded that the learning media developed is valid and quite feasible to be used in the learning process. This research contributes to the enrichment of innovative learning media studies, particularly in integrating digital applications such as Filmora into Indonesian language learning. The implications of this study highlight the potential for educators to adopt similar digital-based approaches in order to enhance students’ engagement and creativity in learning drama materials.